La Falta de Tipificación del Delito de Estafa informática en el Código Orgánico Integral Penal (COIP), perjudica el Patrimonio de las personas. - Medina González, Claudia Karina (2021)
The advances in information and communication technology evolve day after day, providing facilities in various aspects of life and in the development of the Society, but at the same time they have brought certain disadvantages due to having the characteristic of free access, giving lead to the emergence of new forms of crime or in turn an evolution of the forms of committing illicit activities; due to the number of personal information that the user enters, in the variety of applications that technology offers, such as popular social networks or online purchases. These behaviors that I speak of in this research work as the object of this research considering that they are the following: The insertion of fraudulent links in social networks and emails to obtain personal and confidential information, job offers or data updating (Phishing), the insertion of fraudulent links or messages through mobile telephony to obtain personal and confidential information, a common form is the promises of having won a prize of considerable value (Smishing); and, finally, the use of calls programmed simultaneously to different numbers, by means of which the user is obliged to call the assigned number under penalty of seeing his assets in his bank account harmed (Vishing), behaviors that doctrinally and in other laws known or typified as a computer scam. Our country typifies in Article 186 of the current Comprehensive Organic Criminal Code actions similar to the behaviors mentioned above in its numeral 2, referring to the common fraud, fraud in devices for banking use specifically "bank teller", damage or deception to the consumer among others, which causes the State Attorney General's Office to adapt other forms of computer fraud in this criminal type of common fraud. 6 Throughout the development of this research, I will address and develop issues that will allow a differentiation between the crime of common fraud and computer fraud, the importance that is classified independently in our Comprehensive Organic Criminal Code, computer fraud; considering that it is a product of the advances of information and communication technologies, focused on producing an impact on people's assets. This work is initially developed with a brief historical review of the evolution of technologies from their discovery, their types and uses that are given to each one, until determining the elements that must be present for the crime of common scam and computer scam supported by a study and description of each of the types of computer scam main topic of this research, as well as a differentiation between both crimes. Without neglecting the analysis of our constitutional legislation to identify the protected asset that is affected by the crime of computer fraud, and how it relates to legal security, the principle of legality and the literal interpretation of the law, stipulated in its Article 13 and 5, subsection 1, respectively articulated pertaining to the Comprehensive Organic Criminal Code. Without leaving aside the international normative resources granted by the Law, whose value is very high in the present investigation due to its referential contribution such as the Convention on Cybercrime celebrated in Budapest for European countries and a source of guidance for legislation of countries that do have criminalization the crime of computer fraud in a more autonomous and independent way than the crime of common fraud. 7 I conclude with the presentation of a legal reform proposal according to the current social and technological reality, based on reasons and foundations extracted from the legal study, with respect to the constitutional mandates, being the principle of legality, one of the fundamental principles to be able to sanction to a person, and the literal interpretation of the rule. With this, the need to implement the figure of computer fraud and its modalities within the catalog of computer crimes is not questioned, in order to guarantee the protection of people's assets and property.